2012
DOI: 10.1017/s0007114512003686
|View full text |Cite
|
Sign up to set email alerts
|

Mini Nutritional Assessment predicts gait status and mortality 6 months after hip fracture

Abstract: The aim of the present study was to evaluate the Mini Nutritional Assessment (MNA), the Nutritional Risk Screening (NRS) 2002 and the American Society of Anesthesiologists Physical Status Score (ASA) as predictors of gait status and mortality 6 months after hip fracture. A total of eighty-eight consecutive patients over the age of 65 years with hip fracture admitted to an orthopaedic unit were prospectively evaluated. Within the first 72 h of admission, each patient's characteristics were recorded, and the MNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(44 citation statements)
references
References 22 publications
4
38
0
2
Order By: Relevance
“…192 Another recent study showed the Mini Nutritional Assessment to be predictive of gait status and mortality at 6 months after hip fracture. 193 Cost-effectiveness of nutritional interventions has been studied as well and found to be effective at 3 months when the result was weight gain. 194 However, the authors noted no improvement in quality-adjusted life-years.…”
Section: Stephen L Kates Md and Amy Kates Ms Rn-bcmentioning
confidence: 99%
“…192 Another recent study showed the Mini Nutritional Assessment to be predictive of gait status and mortality at 6 months after hip fracture. 193 Cost-effectiveness of nutritional interventions has been studied as well and found to be effective at 3 months when the result was weight gain. 194 However, the authors noted no improvement in quality-adjusted life-years.…”
Section: Stephen L Kates Md and Amy Kates Ms Rn-bcmentioning
confidence: 99%
“…In the past three years both long and short forms of the MNA have been used to examine the association of nutritional status with outcomes in hip fracture patients. (4,(19)(20)(21). Gumiero et al (19) established that MNA-LF is good for predicting gait status and mortality.…”
Section: Introductionmentioning
confidence: 99%
“…(4,(19)(20)(21). Gumiero et al (19) established that MNA-LF is good for predicting gait status and mortality. In a study by Bell and associates (20) American Society of Anesthesiologists (ASA) scores were used to assess general health status and severity of physical comorbidity (23) in five classes: 1) healthy < 65 years, 2) mild systemic disease, 3) severe systemic disease, 4) severe systemic disease that is a constant threat to life and 5) moribund and not expected to survive without surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Malnutrition is associated with many adverse outcomes including depression of the immune system, impaired wound healing, muscle wasting, longer lengths of hospital stay, higher treatment costs and increased mortality 6 . Malnutrition in hip fracture patients is associated with adverse rehabilitation outcomes [7][8][9][10][11] . Moreover, malnourished individuals in all settings use more healthcare resources and experience poor life quality 12 .…”
Section: Jfsf 40mentioning
confidence: 99%